A realization of cultural diversity in command speech acts: A sociopragmatics study - Pujiati Tri; Syarifudin Achmad; Arjulayana Achmad; Hisyam Mohamad Ali; Rohman M. Fathor (BIO Web of Conferences)
A command speech act is one of directive utterances found in many activities which have the potential to threaten partners. This study investigates politeness strategies in command speech acts among male and female Indonesian students from diverse cultural backgrounds. Furthermore, this study tries to find out if there is significance differences on politeness strategy used by students based on gender perspective. The research method used is a mix method by using sociopragmatics approach. The data in this study were obtained by using opened Discourse Completion Test (DCT), which was designed to get information about the politeness strategy used by students based on situation given in DCT. The samples of this study are 30 female and male. The results of the study prove that (1) the use of negative politeness strategy at about 93.73%, positive politeness strategies 4.90%, and bald on record strategies 1,37%; (2) based on the statistic, it can be seen that asymp.sig is 0,470, the score of asymp.sig >0,05, it means that Ha rejected, so it can concluded that there is no significance differences on the type and frequency of politeness strategy used by students in implementing command speech acts. This study gives implication that the medical students from different gender can decide appropriate politeness strategy when they command a partner.